2021
DOI: 10.1186/s40510-021-00387-z
|View full text |Cite
|
Sign up to set email alerts
|

Validating clinical characteristics of primary failure of eruption (PFE) associated with PTH1R variants

Abstract: Background Primary failure of eruption (PFE) is a hereditary condition, and linkage with variants in the PTH1R gene has been demonstrated in many cases. The clinical severity and expression of PFE is variable, and the genotype–phenotype correlation remains elusive. Further, the similarity between some eruption disorders that are not associated with PTH1R alterations is striking. To better understand the genotype–phenotype correlation, we examined the relationship between the eruption phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
1
18
0
4
Order By: Relevance
“…9,31 A classic diagnostic feature proposed by Rhoads et al 32 is the frequent involvement of the first molar along with the adjacent teeth in an unusual supracrestal position. A recent systematic review by Hanisch et al 9 identified bilateral infraocclusion of the posterior teeth as a hallmark According to the diagnostic rubrics, 12,33 our patient had the following radiological/clinical signs:…”
Section: Diagnostic Challengesmentioning
confidence: 81%
See 4 more Smart Citations
“…9,31 A classic diagnostic feature proposed by Rhoads et al 32 is the frequent involvement of the first molar along with the adjacent teeth in an unusual supracrestal position. A recent systematic review by Hanisch et al 9 identified bilateral infraocclusion of the posterior teeth as a hallmark According to the diagnostic rubrics, 12,33 our patient had the following radiological/clinical signs:…”
Section: Diagnostic Challengesmentioning
confidence: 81%
“…According to the diagnostic rubrics, 12,33 our patient had the following radiological/clinical signs: The teeth of the posterior region are affected more frequently (first and second molars more often than premolars or canines) Affected teeth were resorbing the alveolar bone coronal but do not erupt totally or erupt incomplete Mostly the clinical findings were asymmetric, which means there was a bilaterally unbalanced eruption of the teeth. Vertically, there is was an impairment of growth of the alveolar bone in the affected region A severe lateral open bite in the affected region …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations